Effect of Aging Treatment and TiO2 Nano Particles Addition on the Microstructure and Mechanical Properties of 2024 Aluminum Alloy - mahan, Hamid (International Journal of Integrated Engineering, 2024)
In this study we reinforced aluminum alloy 2024 with the different mass fractions (0 wt.%, 2.5 wt.%, 5 wt.% and 7.5 wt.%) of titanium dioxide nanoparticles using stir casting method followed by solution annealing at 500 °C for 3 h, quenching in water and aging at 175°C for 3 h. The main objective was to study an effect of an addition of TiO2 nanoparticles on the microstructure and the mechanical properties of the 2024 aluminum alloy composite fabricated by stir casting. Scanning electron microscopy, energy-dispersive analysis, as well as X-ray diffraction analysis were implemented to characterize the microstructure, elemental and phase composition of the samples. The tensile and Vickers hardness tests were carried out to evaluate the mechanical properties. The results showed that the addition of 7.5 wt.% TiO2 nanoparticles increases the ultimate tensile strength by 37 % and elongation by 71 % while decreases the hardness by 14 % comparing with the initial alloy. The highest hardness was demonstrated in the alloy with 5 wt. % TiO2.